2019
DOI: 10.1002/cbic.201900504
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Binding Interactions of Teixobactin with the Bacterial Cell‐Wall Precursor Lipid II

Abstract: The prevalence of life‐threatening, drug‐resistant microbial infections has challenged researchers to consider alternatives to currently available antibiotics. Teixobactin is a recently discovered “resistance‐proof” antimicrobial peptide that targets the bacterial cell wall precursor lipid II. In doing so, teixobactin exhibits potent antimicrobial activity against a wide range of Gram‐positive organisms. Herein we demonstrate that teixobactin and several structural analogues are capable of binding lipid II fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…Alternatively, it has been proposed that AMPs cause microbial death via interaction with intracellular targets by inhibiting cell wall, DNA, RNA, and/or protein synthesis [37][38][39]. Examples of AMPs with intracellular targets include teixobactin that prevents cell wall synthesis by binding the peptidoglycan precursor lipid II [40], indolicidin that binds to DNA thereby inhibiting DNA replication [41], the larvae peptide Lser-PRP2 that is suggested to inhibit protein folding by binding to the bacterial chaperone DnaK [42], and the proline-rich peptide Bac5 that blocks translation by binding to ribosomes [43].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it has been proposed that AMPs cause microbial death via interaction with intracellular targets by inhibiting cell wall, DNA, RNA, and/or protein synthesis [37][38][39]. Examples of AMPs with intracellular targets include teixobactin that prevents cell wall synthesis by binding the peptidoglycan precursor lipid II [40], indolicidin that binds to DNA thereby inhibiting DNA replication [41], the larvae peptide Lser-PRP2 that is suggested to inhibit protein folding by binding to the bacterial chaperone DnaK [42], and the proline-rich peptide Bac5 that blocks translation by binding to ribosomes [43].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a collaborative effort between the Cochrane, Payne, Martin and Vederas groups, and the Ferring Research Institute, showed that H-TriA 1 significantly improves the antimicrobial activity of teixobactin analogues to include Gram-negative strains. 34 Perhaps the most significant observation was a 125-fold decrease in MIC of native teixobactin against Salmonella enterica when co-administered with H-TriA 1 at 12.5 μg mL −1 .…”
Section: Resurgence Of the Tridecaptins: Establishing A Structure–activity Relationshipmentioning
confidence: 99%
“…In addition, brevibacillin 2V also showed binding to membrane-embedded Lipid II, albeit with somewhat lower affinity with a Kd value of 7.9 μm (Figure 5B). Nisin, teixobactin, nukacin ISK-1, and lacticin 3147 are wellknown Lipid II-binding antibiotics; among these antibiotics, nisin showed the strongest binding affinity to membraneembedded Lipid II with a Kd value of 14.6 nm, and lacticin 3147 showed the lowest binding affinity to membrane-embedded Lipid II with a Kd value of 0.92 μm (Islam et al, 2012;'t Hart et al, 2016;Bakhtiary et al, 2017;Chiorean et al, 2020). In this study, brevibacillins showed solid-binding affinities (Kd, 0.9 μm to 7.9 μm), and they were reported to have comparable antimicrobial activities as nisin and lacticin 3147 against the tested bacterial pathogens .…”
Section: Brevibacillin and Brevibacillin 2v Show Good Affinity To Lipid IImentioning
confidence: 99%